Cost and cost-effectiveness of interim methadone treatment and patient navigation initiated in jail. (1st December 2020) - Zarkin, Gary A.; Orme, Stephen; Dunlap, Laura J.; Kelly, Sharon M.; Mitchell, Shannon G.; O'Grady, Kevin E.; Schwartz, Robert P.
Highlights: Jail-based methadone combined with patient navigation is a low cost intervention. Estimated navigation costs were 283 per patient for 3 months. Methadone combined with patient navigation is almost certainly cost-effective. Abstract: Background: Individuals with opioid use disorder (OUD) who are released from pre-trial detention in jail have a high risk of opioid relapse. While several interventions for OUD initiated during incarceration have been studied, few have had an economic evaluation. As part of a three-group randomized trial, we estimated the cost and cost-effectiveness of a negative urine opioid test. Detainees were assigned to interim methadone (IM) in jail with continued methadone treatment post-release with and without 3 months of post-release patient navigation (PN) compared to an enhanced treatment-as-usual group. Methods: We implemented a micro-costing approach from the provider's perspective to estimate the cost per participant in jail and over the 12 months post-release from jail. Economic data included jail-based and community-based service utilization, self-reported healthcare utilization and justice system involvement, and administrative arrest records. Our outcome measure is the number of participants with a negative opioid urine test at their 12-month follow-up. We calculated incremental cost-effectiveness ratios (ICERs) for intervention costs only and costs from a societal perspective. Results: The average cost of providing patient navigation services per individual beginning in jail and continuing in the community was 283. We find that IM is dominated by ETAU and IM + PN. Per additional participant with a negative opioid urine test, the ICER for IM + PN including intervention costs only is 91 and 305 including societal costs. Conclusions: IM + PN is almost certainly the cost-effective choice from both an intervention provider and societal perspective.